2015
DOI: 10.1002/hpm.2331
|View full text |Cite
|
Sign up to set email alerts
|

Lean healthcare in developing countries: evidence from Brazilian hospitals

Abstract: The present study evaluates how five sectors of two Brazilian hospitals have implemented lean healthcare concepts in their operations. The main characteristics of the implementation process are analyzed in the present study: the motivational factor for implementation, implementation time, form (consultancy or internal), team (hospital and consultants), lean implementation continuity/sustainability, lean healthcare tools and methods implemented, problems/improvement opportunities, lean healthcare barriers faced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
26

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 59 publications
1
76
0
26
Order By: Relevance
“…Lean management is considered a management system aims to organize the operation design which reduced waste and time-consuming, improved safety and quality, and decreased the costs in health industries by using several tools such as Fishbone, flow chart in addition to redesign the operational work (Costaet al, 2017;D'Andreamatteo et al, 2015). Many health organizations such as National Health Service (NHS) and Institute for Healthcare Improvement (IHI) have recommended utilizing the lean concepts in health setting to enhance work efficiency (Costa et al, 2017;D'Andreamatteo et al, 2015;Machado et al, 2013;Sloan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lean management is considered a management system aims to organize the operation design which reduced waste and time-consuming, improved safety and quality, and decreased the costs in health industries by using several tools such as Fishbone, flow chart in addition to redesign the operational work (Costaet al, 2017;D'Andreamatteo et al, 2015). Many health organizations such as National Health Service (NHS) and Institute for Healthcare Improvement (IHI) have recommended utilizing the lean concepts in health setting to enhance work efficiency (Costa et al, 2017;D'Andreamatteo et al, 2015;Machado et al, 2013;Sloan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The literature showed that lean healthcare has been growing into a significant strand of research and quality projects in the early 2,000s.it is considered a most common tool used to ensure cost effectiveness and removal of wastes, and to enhance patient and employee satisfaction. (Costa et al, 2017;D'Andreamatteo et al, 2015;Lawal et al, 2014;Sloan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with previous reports, these teams were formed and conducted the projects in the three studied cases. In agreement with Costa et al (2015) and Bertani (2012), employee commitment was the critical factor for LP implementation in the three studied cases. In addition, as suggested by Zidel (2006), LP implementation began with the contracting of a consulting company.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 74%
“…For instance, Brown et al, (2014) tested the versatility of Sus-VSM framework for three case studies with different product varieties and product volumes and concluded in favor of sufficient versatility [184]. Moreover, some past studies also highlighted that each paradigm comes with its own sector and organization-specific internal and external barriers that need to be well-understood for successful implementation [11,90,118,[185][186][187][188][189][190][191]. Barriers include, but are not limited to, factors such as the cost of implementation/transformation, lack of awareness/education/dedication of workforce and partners, intra-/inter-organizational network complexity, and insufficient communication and transparency [5,62,[192][193][194][195].…”
Section: Versatility Organizational Culture and Deployment Plan Conmentioning
confidence: 99%